Regulation—the real threat to clinical research. (16th October 2008) - Stewart, Paul M; Stears, Anna; Tomlinson, Jeremy W; Brown, Morris J
Abstract : Recent changes to research governance were intended to ensure that clinical trials are safe and effective. But Paul Stewart and colleagues argue that the regulatory burden is now obstructing high quality science